Effect of hydrogen sulfide on the contractile activity of smooth muscle cells from the rat aorta - M. B. Baskakov; S. V. Gusakova; A. S. Zheludeva; L. V. Smagly; I. V. Kovalyov; T. A. Vtorushina; D. S. Nosov; K. V. Yeryomenko; M. A. Medvedev; S. N. Orlov (Бюллетень сибирской медицины)
In preparations of rat aorta, used as a model of muscular type arteries, the method mehanografii studied the effect of hydrogen sulfide on the reduction of isolated of vascular smooth muscle. Found that hydrogen sulfide in concentrations 1—50 mmol increases the mechanical stress of smooth muscle in high-K + medium. At higher concentrations (300—1 000 mmol) H2S leads to lower amplitude giperkalievoy contraction in high-K + medium. Reduction of smooth muscle cells caused by phenylephrine inhibited the action of hydrogen sulfide in the whole range of concentrations. The causes of differences in data obtained with the results of studies in other laboratories, and possible mechanisms of action of hydrogen sulfide on the contractile activity of vascular smooth muscle.